2007
DOI: 10.1167/iovs.06-0923
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor/Scatter Factor Promotes Retinal Angiogenesis through Increased Urokinase Expression

Abstract: These studies suggest that HGF may play an important role in the initial stages of retinal angiogenesis by stimulating a migratory phenotype in endothelial cells mediated by increased urokinase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 47 publications
2
27
0
2
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) is the growth factor of primary importance in driving the angiogenic process forward in most tissues. 45 VEGF interacting with its receptor VEGFR-2 rapidly induces prourokinase (pro-u-PA) activation on the surface of endothelial cells, which involves a phosphatidylinositol 3-kinase (PI3k)-dependent change in integrin affinity. 46,47 A large body of experimental evidence from in vitro and in vivo studies indicates that, in VEGFinduced endothelial cell migration and angiogenesis, the u-PA/u-PAR system, especially the presence of u-PAR, seems to be essential, because their inhibition can result in the significant decrease of tumor neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is the growth factor of primary importance in driving the angiogenic process forward in most tissues. 45 VEGF interacting with its receptor VEGFR-2 rapidly induces prourokinase (pro-u-PA) activation on the surface of endothelial cells, which involves a phosphatidylinositol 3-kinase (PI3k)-dependent change in integrin affinity. 46,47 A large body of experimental evidence from in vitro and in vivo studies indicates that, in VEGFinduced endothelial cell migration and angiogenesis, the u-PA/u-PAR system, especially the presence of u-PAR, seems to be essential, because their inhibition can result in the significant decrease of tumor neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…This includes not only mild infiltration of macrophages and accumulation of microglia, but also the presence of inflammatory components such as complement factors, pro-inflammatory cytokines, and chemokines. Many growth factors have been shown to be involved in the development of retinal neovascularization, including vascular endothelial growth factor (VEGF), pigment epithelium-derived factor (PEDF), basic fibroblast growth factor (bFGF, FGF-2), hepatocyte growth factor (HGF), tumor necrosis factor alpha (TNF-α), and others (Kwak et al, 2000; Spilsbury et al, 2000; Lip et al, 2001; Amin et al, 1994; Tomita et al, 2003; Colombo et al, 2007; Qazi et al, 2009; Hu et al, 2009; Dias et al, 2011). A study of genetic linkage and allelic association has identified VEGF, low density lipoprotein receptor-related protein 6 (LRP6) and very low-density lipoprotein receptor (VLDLR) as candidate genes in AMD (Haines et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…кроме того, Vegf стимулирует экспрессию урокиназы в сосуди-стых эндотелиальных клетках [167]. Ангиоге-нез в сетчатке, индуцированный hgf, также опосредован увеличением активности уроки-назы [168]. нарушение взаимодействия уро-киназы с ее рецептором ингибирует усиление миграционной и инвазивной активности эн-дотелиальных клеток под действием hgf.…”
Section: рис 11 механизмы регуляции роста и ремоделирования артерийunclassified